cos θ 1 + cos θ 2 + cos θ 3
Given that cos ( θ 1 − θ 2 ) + cos ( θ 2 − θ 3 ) + cos ( θ 3 − θ 1 ) = − 2 3 , find the value of the expression above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution. You can even do it another way.
Log in to reply
@Surya Prakash I think it isn't good to repeat essentially the same problem, your 3rd problem is a repeat for this.
Let a , b , c be three complex numbers such that a = e θ 1 i , b = e θ 2 i and c = e θ 3 i . Then let's find the magnitude of their sum, i.e., ∣ a + b + c ∣ :
∣ a + b + c ∣ = ∣ cos θ 1 + cos θ 2 + cos θ 3 + i ( sin θ 1 + sin θ 2 + sin θ 3 ) ∣ a + b + c ∣ = ( cos θ 1 + cos θ 2 + cos θ 3 ) 2 + ( sin θ 1 + sin θ 2 + sin θ 3 ) 2 ∣ a + b + c ∣ = 3 + 2 ( cos θ 1 cos θ 2 + sin θ 1 sin θ 2 + cos θ 2 cos θ 3 + sin θ 2 sin θ 3 + cos θ 3 cos θ 1 + sin θ 3 sin θ 1 ) ∣ a + b + c ∣ = 3 + 2 ( cos ( θ 1 − θ 2 ) + cos ( θ 2 − θ 3 ) + cos ( θ 3 − θ 1 ) ) ∣ a + b + c ∣ = 3 + 2 ( − 2 3 ) ∣ a + b + c ∣ = 0 ⟹ a + b + c = 0
Hence, cos θ 1 + cos θ 2 + cos θ 3 + i ( sin θ 1 + sin θ 2 + sin θ 3 ) = 0 . Comparing the real part we get 0 as our answer.
Nice solution!
cos ( θ 1 − θ 2 ) + cos ( θ 2 − θ 3 ) + cos ( θ 3 − θ 1 ) = − 2 3
⟹ 3 + 2 [ cos ( θ 1 − θ 2 ) + cos ( θ 2 − θ 3 ) + cos ( θ 3 − θ 1 ) ] = 0
⟹ ( sin 2 ( θ 1 ) + cos 2 ( θ 1 ) ) + ( sin 2 ( θ 2 ) + cos 2 ( θ 2 ) ) + ( sin 2 ( θ 3 ) + cos 2 ( θ 3 ) ) + 2 cos ( θ 1 ) cos ( θ 2 ) + 2 sin ( θ 1 ) sin ( θ 2 ) + 2 cos ( θ 2 ) cos ( θ 3 ) + 2 sin ( θ 2 ) sin ( θ 3 ) + 2 cos ( θ 3 ) cos ( θ 1 ) + 2 sin ( θ 3 ) sin ( θ 1 ) = 0
⟹ ( sin 2 ( θ 1 ) + sin 2 ( θ 2 ) + sin 2 ( θ 3 ) + 2 sin ( θ 1 ) sin ( θ 2 ) + 2 sin ( θ 2 ) sin ( θ 3 ) + 2 sin ( θ 3 ) sin ( θ 1 ) ) + ( cos 2 ( θ 1 ) + cos 2 ( θ 2 ) + cos 2 ( θ 3 ) + 2 cos ( θ 1 ) cos ( θ 2 ) + 2 cos ( θ 2 ) cos ( θ 3 ) + 2 cos ( θ 3 ) cos ( θ 1 ) ) = 0
⟹ ( sin ( θ 1 ) + sin ( θ 2 ) + sin ( θ 3 ) ) 2 + ( cos ( θ 1 ) + cos ( θ 2 ) + cos ( θ 3 ) ) 2 = 0
⟹ cos ( θ 1 ) + cos ( θ 2 ) + cos ( θ 3 ) = sin ( θ 1 ) + sin ( θ 2 ) + sin ( θ 3 ) = 0
Problem Loading...
Note Loading...
Set Loading...
P = [ cos θ 1 cos θ 2 + sin θ 1 sin θ 2 ] + [ cos θ 2 cos θ 3 + sin θ 2 sin θ 3 ] + [ cos θ 3 cos θ 1 + sin θ 3 sin θ 1 ] P = [ cos θ 1 cos θ 2 + cos θ 2 cos θ 3 + cos θ 3 cos θ 1 ] + [ sin θ 1 sin θ 2 + sin θ 2 sin θ 3 + sin θ 3 sin θ 1 ] P = 2 ( cos θ 1 + cos θ 2 + cos θ 3 ) 2 − cos 2 θ 1 − cos 2 θ 2 − cos 2 θ 3 + 2 ( sin θ 1 + sin θ 2 + sin θ 3 ) 2 − sin 2 θ 1 − sin 2 θ 2 − sin 2 θ 3 P = 2 ( cos θ 1 + cos θ 2 + cos θ 3 ) 2 + ( sin θ 1 + sin θ 2 + sin θ 3 ) 2 − 3 = − 2 3
( cos θ 1 + cos θ 2 + cos θ 3 ) 2 + ( sin θ 1 + sin θ 2 + sin θ 3 ) 2 = 0
cos θ 1 + cos θ 2 + cos θ 3 = 0